Evaluation of implant-associated complications after mesh-implants setting in pelvic floor reconstruction - Alfiya G Yashchuk; Ilnur I Musin; Raisa A Naftulovich; Elena M Popova; Irina B Fatkullina; Dina F Absalyamova; Kseniya A Kamalova; Anzhella R Molokanova; Kseniya N Yashchuk (IP Berlin A.V., 2019)
Relevance. According to world data, nowadays prevalence of pelvic floor dysfunction and pelvic organ prolapsed reaches 28%. Most specialists relate pregnancy and delivery to main factors of pelvic prolapse development. Due to lifespan growth frequency of pelvic organ prolapse development increases. According to FDA data annually in the world is made more than 100 000 surgeries with synthetic implants, herewith heavy complications occur in 3.4% and mild complications occur in 14.8% of all cases. About 58% of surgeries are made to women under the age of 60, 13% of patients needs re-intervention during next 5 years. It should be noted that in cases of relapse more than 30% of women need re-intervention. Aim. Evaluate implant-associated complications after mesh-implants setting. Materials and methods. We have made retrospective analysis of mesh-implant use in 458 patients with pelvic organ prolapse in 2018-2018 yy. on the base of Bashkir State Medical University clinic. In order to assess quality of life after mesh-implant setting, we used the following questionnaires: Incontinence Questionnaire Short Form (ICIQ-SF), and also Female Sexual Function Index (FSFI). In order to assess blood microcirculation indices after surgery, we used laser Doppler flowmetry evaluation from anterior vaginal wall. Results. All in all, there were revealed 13 (2.84%) implant-associated complications. In 4 patients ICIQ-SF points were from 3 to 15, which indicates manifestation of urgent urine incontinence signs. According to FSFI questionnaire, sexually active women have 31.5 points. Basic factor, which provokes pelvic floor muscles dysfunction is delivery. Besides, in group of women of reproductive age, pelvic floor muscles dysfunction (PFMD) is associated with the presence of concomitant gynecologic diseases (uterine myoma, endometriosis, ovarian tumors). In the group of women older than 45 years with the presence of somatic pathology - obesity and impaired blood circulation. According to LDF data from anterior vaginal wall women with PFMD have low blood circulation indices, herewith the lowest indices are registered in the group of women older than 45 years.